Structure of the set of Borel exceptional vectors for entire curves - A.I. Bandura; Ya.I. Savchuk (Математичні Студії, 2020)
It is proved that the structure of the set of Borel exceptional vectors for transcendental entire curve something likes structure of the set of Nevanlinna deficient vectors for entire curve of finite order.